Agrotis volubilis Harvey, Voluble Dart 1874 - Pogue, Michael G. (Zenodo, 2006)
10. Agrotis volubilis Harvey, Voluble Dart (adult) (Fig. 12) Identification: Forewing length 14.0–18.0 mm. The males have biserrate antennae. Forewing is dark gray in the costal half to the reniform spot, the rest pale rufous. Orbicular spot is ovate, reniform spot is dark gray, claviform spot is an elongate dash; all are outlined in black. Terminal area of forewing has a series of black triangular spots with second and third the largest. Hindwing is white with darker veins and darker scaling along the costa and outer margins. Flight period: MidMay to early July. Collected localities: This species is not recorded from the Park, but it is likely to occur there. General distribution: Widespread in North America from Newfoundland to British Columbia in Canada and in the United States from Maine to Florida and west to the West Coast (Lafontaine 2004). Larval hosts: Polyphagous; hosts include alfalfa ( Medicago sativa L., Fabaceae), beans ( Phaseolus sp., Fabaceae), chickweed ( Cerastium sp., Caryophyllaceae), clover ( Trifolium sp., Fabaceae), corn ( Zea mays L., Poaceae), little barley ( Hordeum pusillum Nutt., Poaceae), and tobacco ( Nicotania sp., Solanaceae). Published as part of Pogue, Michael G., 2006, The Noctuinae (Lepidoptera: Noctuidae) of Great Smoky Mountains National Park, U. S. A., pp. 1-95 in Zootaxa 1215 (1) on page 22, DOI:10.11646/zootaxa.1215.1.1, http://zenodo.org/record/5064764